2021
DOI: 10.1007/s00508-021-01875-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the male and female reproductive systems induced by COVID-19

Abstract: A variety of pneumonia cases of unknown cause emerged in China in December 2019. A new virus belonging to the Coronaviridae family, called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 . Within a few days, COVID-19 became a pandemic disease. This review aimed to investigate the possible implications of COVID-19 for human reproductive systems, as in previous studies ACE2 was highly expressed in some organs of these systems, such as the testicles. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The effect of the functionality is potentiated by the reduction of zinc in the conditions of the cytokine storm and the appearance of reactive oxygen species [ 30 ]. Thus, a special attention should be given to fertile women to highlight potential ovarian damages [ 31 , 32 ]. A possible explanation of spontaneous abortions reported at the patients diagnosed with COVID-19 infection is given by the fact that ACE2 receptors are also found at the endometrium, which could negatively interfere with embryo implantation [ 33 ].…”
Section: Covid-19 and The Female Reproductive Systemmentioning
confidence: 99%
“…The effect of the functionality is potentiated by the reduction of zinc in the conditions of the cytokine storm and the appearance of reactive oxygen species [ 30 ]. Thus, a special attention should be given to fertile women to highlight potential ovarian damages [ 31 , 32 ]. A possible explanation of spontaneous abortions reported at the patients diagnosed with COVID-19 infection is given by the fact that ACE2 receptors are also found at the endometrium, which could negatively interfere with embryo implantation [ 33 ].…”
Section: Covid-19 and The Female Reproductive Systemmentioning
confidence: 99%
“… 16 In addition, in some studies, increased serum luteinizing hormone (LH) concentrations have been observed in men and women infected with COVID-19, which indicates the possibility of hypogonadism. 17 Other serum markers related to reproductive function, such as type 2 cysteine, are rarely mentioned in the literature, but they may also be affected by COVID-19. 18 Therefore, the purpose of this study was to explore the effects of mild/asymptomatic COVID-19 on semen parameters and sex-related hormone levels and to analyze the relationship between semen parameter values and semen collection time after infection, fever, and severity of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 39 These changes might be related to the rise of body temperature caused by COVID-19. 40 Opinions differ on the presence of SARS-CoV-2 in semen, with most scholars holding negative views, 41–44 but, nevertheless, some scholars have detected the genetic materials of SARS-CoV-2 in semen. 40 …”
Section: Discussionmentioning
confidence: 99%